Intervensi Art Therapy untuk Meningkatkan Self Esteem pada Pasien Dewasa Skizofrenia Paranoid - Harniati, Yunia; Dinni, Siti Muthia (Universitas Muhammadiyah Metro, 2024)
Schizophrenia is a psychotic disorder that arises from vulnerability or predisposition to developmental disorders and is also usually genetic. In overcoming paranoid schizophrenia, it can be done with art therapy. This study aims to determine the effectiveness of art therapy to increase self-esteem in paranoid schizophrenia patients. The research subject was a patient of